Contemporary outcomes of mitral valve repair for degenerative disease in the era of increased penetrance of percutaneous mitral valve technologyCentral MessagePerspective - Brittany G. Abt, MD; Michael E. Bowdish, MD, MS; Ramsey S. Elsayed, MD, MD; Robbin Cohen, MD; Markian Bojko, MD, MPH; Alexander Vorperian, BS; Michael Brown, BS; Vaughn A. Starnes, MD (JTCVS Open, 2023)
Objective: The study objective was to evaluate the surgical outcomes of mitral valve repair in the era of percutaneous technology. Methods: We retrospectively reviewed 452 patients who underwent mitral valve repair for degenerative disease between 2010 and 2021. Survival, mitral valve reoperation, and mitral regurgitation recurrence were assessed using Cox regression, dichotomized for those aged more than or less than 60 years. Results: Median age in years (interquartile range) was 52 (47-57) in the younger cohort and 67 (63-73) in the older cohort (P < .0001). Preoperative comorbidities and leaflet pathology were comparable between groups. After adjustment for sex, prior sternotomy, diabetes, atrial fibrillation, and type of leaflet repair, age 60 years or more was not associated with increased mortality (hazard ratio, 6.96, 95% confidence interval, 0.85-56.8, P = .07). Considering death as a competing outcome, cumulative incidence of mitral valve reoperation at 1, 3, and 5 years was 0.9%, 1.4%, and 1.8% in the younger cohort, respectively, and 2.7%, 4.0%, and 5.1% in the older cohort, respectively (subhazard ratio, 2.95, 95% confidence interval, 0.84-10.4, P = .09). Cumulative incidence of mitral regurgitation recurrence with moderate-severe or greater mitral regurgitation at 1, 3, and 5 years was 1.4%, 3.6%, and 5.1%, and 2.7%, 3.5%, and 4.7% in the younger and older cohorts, respectively (subhazard ratio, 0.85, 95% confidence interval, 0.29-2.50, P = .76). Subgroup analysis focusing on isolated mitral valve repairs (n = 388) showed equivalent results with respect to mortality (hazard ratio, 5.31, 95% confidence interval, 0.64-44.0, P = .12), mitral valve reoperation (subhazard ratio, 4.04, 95% confidence interval, 0.89-18.4, P = .07), and mitral regurgitation recurrence (subhazard ratio, 0.98, 95% confidence interval, 0.30-3.15, P = .97). Conclusions: Mitral valve repair outcomes continue to be excellent, even in low-risk patients aged more than 60 years.